2015
DOI: 10.2147/dddt.s92395
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of trabectedin in advanced soft tissue sarcoma: beyond lipo- and leiomyosarcoma

Abstract: 1 (range, 0-5). Median number of trabectedin cycles was 3 (range, 1-17). About 69/72 patients (95.8%) were evaluable for response: 9 patients (13%) achieved partial response and 26 (37.7%) stable disease. According to histotype, clinical benefit (partial response + stable disease) was reported in synovial sarcoma (n=5), retroperitoneal liposarcoma (n=10), myxoid liposarcoma (n=5), leiomyosarcoma (n=8), high-grade undifferentiated pleomorphic sarcoma (n=5), Ewing/ peripheral primitive neuroectodermal tumor (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…The efficacy of this drug in STS, in particular the myxoid liposarcoma histotype, has been demonstrated in numerous clinical trials, but there are also reports of its activity in other sarcoma subtypes. 53 55 Although, there is limited evidence of the impact of trabectedin on MFS, 56 our results are suggestive of some activity in this STS subtype. Moreover, its antitumor activity appears to be related to its direct effect on both cancer cells and the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 58%
“…The efficacy of this drug in STS, in particular the myxoid liposarcoma histotype, has been demonstrated in numerous clinical trials, but there are also reports of its activity in other sarcoma subtypes. 53 55 Although, there is limited evidence of the impact of trabectedin on MFS, 56 our results are suggestive of some activity in this STS subtype. Moreover, its antitumor activity appears to be related to its direct effect on both cancer cells and the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 58%
“…This result is supported by the findings of Sanctis et al, who found that a GMI > 1.33 was associated with significantly improved OS. 15,22 Therefore, the growth-inhibitory effect of trabectedin may have a significant impact on longer patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some small studies have shown the potential usefulness of the drug for the treatment of specific non-L-type sarcoma histotypes such as synovial sarcoma and solitary fibrous tumors (SFTs). 15 18 Trabectedin has also been approved for the treatment of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%